TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HUKUM TENAGA KERJA ASING (TKA) DI INDONESIA DALAM PERSPEKTIF ASAS KEADILAN DAN KEPASTIAN HUKUM - Nurjannah, Risa (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Foreign Workers (TKA) are non-Indonesian nationals employed in Indonesia under valid work permits, as regulated by Law Number 13 of 2003 on Manpower. Their presence is essential to fill specialized roles that cannot yet be fulfilled by local workers and to support knowledge and technology transfer. Consequently, many companies in Indonesia rely on foreign professionals to boost their competitiveness. According to Indonesia’s Ministry of Manpower, the number of Foreign Workers (TKA) in 2023 reached 183,964, showing an 8.9% increase from the previous year. This research adopts a normative juridical approach to examine how the principles of justice and legal certainty are applied in the regulation of foreign employment. Article 27 paragraph (2) of the 1945 Constitution guarantees the right to work and a decent livelihood for all individuals, including foreign nationals. Thus, the government is obliged to ensure fair and equal treatment for both foreign and local workers within employment relationships.